Development of cloud removal and land cover Change extraction algorithms for remotely-sensed Landsat imagery - Usman, Ahmad Basyiruddin (Curtin University, 2011)
Land cover change monitoring requires the analysis of remotely-sensed data. In the tropics this is difficult because of persistent cloud cover, and data availability. This research focuses on the elimination of cloud cover as an important step towards addressing the issue of change detection. The result produced clearer images, whereas some persistent cloud remains. This persistent cloud and the cloud adjacency effects diminish the quality of image product and affect the change detection quality.